Intranasal Administration of the Antisecretory Peptide AF-16 Reduces Edema and Improves Cognitive Function Following Diffuse Traumatic Brain Injury in the Rat - Clausen, Fredrik; Hansson, Hans-Arne; Raud, Johan; Marklund, Niklas (Frontiers in Neurology, 2017)
A synthetic peptide with antisecretory activity, AF-16, improves injury-related deficits in water and ion transport and decreases intracranial pressure after experimental cold lesion injury and encephalitis although its role in traumatic brain injury (TBI) is unknown. AF-16 or an inactive reference peptide was administrated intranasally 30 min following midline fluid percussion injury (mFPI; n=52), a model of mild-moderate diffuse TBI in rats. Sham-injured (n=14) or naïve (n=24) animals were used as controls. The rats survived for either 48 h or 15 days. At 48 h, the animals were tested in Morris water maze (MWM) for memory function and brains analyzed for cerebral edema. Here, mFPI induced brain edema compared to sham or naïve controls that was significantly reduced by AF-16 treatment (p<0.05) although MWM performance was not altered. In the 15-day survival groups, the MWM learning and memory abilities as well as histological changes were analyzed. AF-16 treated brain-injured animals shortened both MWM latency and swim path in the learning trials and improved probe trial performance compared to brain-injured controls treated with the inactive reference peptide (p<0.05). A modest decrease by AF-16 on TBI-induced changes in hippocampal glial acidic fibrillary protein (GFAP) staining (p=0.11) was observed. AF-16 treatment did not alter any other immunohistochemical analyses (degenerating neurons, beta-amyloid precursor protein (β-APP) and Olig2). In conclusion, intranasal AF-16 attenuated brain edema and enhanced visuospatial learning and memory following diffuse TBI in the rat. Intranasal administration early post-injury of a promising neuroprotective substance offers a novel treatment approach for TBI.